Dewan Perwakilan Daerah Republik Indonesia : arsitektur histori, peran, dan fungsi DPD RI terhadap daerah di era otonomi daerah - MOHAMAD Yusuf 1989-
Role and position of the Indonesian Regional Representative Council after implementation of bicameralism in Indonesian parliament due to amendment to the Indonesian 1945 Constitution.